Building Disciplinary Language and Literacy in Elementary Teacher Training. (17th June 2018) - Siffrinn, Nicole E.; Lew, Shim
Abstract: Given increased attention to disciplinary literacy in K–5 contexts, there is a need to explore how elementary preservice teachers are trained to engage in disciplinary instruction. The authors present a curriculum for fostering disciplinary language and literacy awareness in elementary teacher preparation. First, they explain how and why they support preservice teachers in critically reflecting on their language experiences. Second, the authors illustrate how they scaffold preservice teachers in moving from merely recognizing the speaking, listening, reading, and writing bound up in disciplinary practices to deconstructing and designing lessons that attend explicitly to the language of the disciplines. The authors conclude by addressing the opportunities and challenges of integrating this work into early childhood education programs.